Determining design thinking elements in chemistry education: A Fuzzy Delphi method - binti Md. Aris, Norliyana; binti Ibrahim, Nor Hasniza; binti Halim, Noor Dayana; binti Rusli, Nurul Hanani; bin Yaakob, Muhammad Nidzam (Eclética Química, 2025)
Creating a high-quality learning environment where students can solve real-world problems and be receptive is essential for fostering students’ innovation competencies. Using appropriate pedagogical strategies and classroom activities is a crucial aspect of Malaysian education. This article uses the Fuzzy Delphi Method (FDM) to design chemistry classroom teaching strategies based on the design thinking paradigm. This research involves 12 experts in purposive sampling to form a diverse panel encompassing expertise in Chemistry Education, Curriculum, Module Development, Research, and Innovation. Using the Fuzzy Delphi method (FDM), the data were analyzed. Four elements for exploratory constructs, two elements for construct interpretation, four elements for ideation, two elements for execution, and three elements for construct evolution met the FDM requirements, according to the findings. Its threshold value is less than 0.2, the expert consensus is less than 75%, and the average score of the fuzzy number is over 0.5. Encouraging design thinking in chemistry classes and thereby enhancing students’ innovation skills, this research unquestionably induces a paradigm shift in teaching practice.